2019
DOI: 10.5430/jnep.v9n9p63
|View full text |Cite
|
Sign up to set email alerts
|

Integrating critical disability perspectives in nursing education

Abstract: Undergraduate nursing education has a duty to make certain that the focus of both nursing practice with disabled people and nursing education are enabling, rather than disabling. However, depictions of disability in nursing education have been identified as inadequate and at times problematic, with insufficient attention paid to disability in curricula. In this paper, we provide an overview of representations of disability in nursing and examine the gaps and inadequacies in nursing education. We also support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is seen that the content related to disability is mainly lacking in nursing education textbooks 38 . These factors affect the knowledge and attitudes of nursing students toward people with disabilities 11 . This study determined that a significant part of the students did not participate in an activity for the benefit of persons with disabilities and did not contribute to realizing an activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is seen that the content related to disability is mainly lacking in nursing education textbooks 38 . These factors affect the knowledge and attitudes of nursing students toward people with disabilities 11 . This study determined that a significant part of the students did not participate in an activity for the benefit of persons with disabilities and did not contribute to realizing an activity.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that nurses are the largest group in the health workforce increases the rate of encountering individuals with disabilities compared to other healthcare professionals. This situation makes nurses a leading profession in meeting the health needs of people with disabilities 11 . However, studies have shown that nurses do not have enough knowledge to care for people with disabilities [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations